Complete mitochondrial genome of banana new pest Basilepta fulvipes (Coleoptera: Eumolpinae) and phylogenetic analysis - Liu, Li-Na; Zheng, Si-Jun; Guo, Zhi-Xiang; Li, Xun-Dong; Li, Jin-Bin; Zeng, Li (Informa UK Limited, 2020)
Basilepta fulvipes (Motschulsky, 1860) is a banana new pest and mainly distributed in Eastern Asia. The complete mitogenome of B. fulvipes (GenBank accession number MT627597) is 15,762 bp in size, including 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs genes and a noncoding D-loop region. The D-loop region is located between 12S rRNA and tRNAIle. The base composition of the whole B. fulvipes mitogenome is 41.66% for A, 8.89% for G, 34.32% for T and 15.12% for C, with a high AT bias of 75.98%. The present data could contribute to further detailed phylogeographic analysis and comprehensive control of this banaba new pest.